The Signifying Self : A Psycho Social Semiotic Analysis of People Watching - Berger, Arthur Asa, (Brill Research Perspectives in Humanities and Social Sciences., 2025)
The Signifying Self is a study in people watching. It uses semiotics, psychoanalytic theory and sociological perspectives to consider how people present themselves to the world and are assessed by those watching them. It deals with people's physical attributes, such as their age, teeth, bodies and the brands of things they wear and use to suggest how those watching them make decisions about them.